2021
DOI: 10.1111/1759-7714.14172
|View full text |Cite
|
Sign up to set email alerts
|

Ureteral metastasis from pulmonary adenocarcinoma: A case report and literature review

Abstract: The occurrence of ureteral metastasis from distant primary tumors is uncommon, and appears to be especially rare when it originates from the lungs. In the case presented here, a patient with lumbago and left hydronephrosis was diagnosed with left ureteral metastasis of pulmonary adenocarcinoma after a CT‐guided percutaneous transthoracic needle biopsy of the lung and retroperitoneal laparoscopic left nephroureterectomy. He accepted the targeted therapy because the lung tumor epidermal growth factor receptor mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…ureter, ureteral, lung cancer, and metastasis, identified 9 publications after exclusion of unavailable or non-English full texts as well as those reporting direct ureteral involvement (Table 1) [6][7][8][9][10][11][12][13]. Two of these were autopsy studies: one reported 2 cases of lung cancer ureteral metastases (and 35 of other origin) among 11,698 patients [14], and the other identified 3 such cases among 3200 patients [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ureter, ureteral, lung cancer, and metastasis, identified 9 publications after exclusion of unavailable or non-English full texts as well as those reporting direct ureteral involvement (Table 1) [6][7][8][9][10][11][12][13]. Two of these were autopsy studies: one reported 2 cases of lung cancer ureteral metastases (and 35 of other origin) among 11,698 patients [14], and the other identified 3 such cases among 3200 patients [15].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, neoplastic cells may infrequently be implanted in the sub-epithelial region, forming a nodule, which is most likely caused by the penetration of cancer cells into the lamina propria by perforating arterioles. Nephroureterectomy is the treatment of choice for ureteral metastases, while palliative chemotherapy is offered to ineligible patients [7,[9][10][11][12]15].…”
Section: Discussionmentioning
confidence: 99%